Formal Acceptance of the Marriage Age Exception in the KUA Kluet Timur - Nurdin, Ridwan; Sufrizal, Sufrizal (Media Syari'ah : Wahana Kajian Hukum Islam dan Pranata Sosial, 2023)
Early marriage is a controversial issue in East Kluet, South Aceh, making it a topic for all social groups. This article examines how the Office of Religious Affairs grants early marriage requests and how the Copying Regulations of Islamic Law affect early childhood marriage. How does Islamic law review early marriage? Discussing this thesis via field research. Primary and secondary data sources According to research, the Office of Religious Affairs makes early marriage simple by granting a letter of dispensation for the former requirements for religious courts for Muslims and district courts for non-Muslims. Second, for the benefit of the family and household, marriage can only be performed by the prospective bride and groom who have reached the age specified in Article 7 of Law Number 1 of 1974, namely the prospective husband. at least 19 and the potential wife at least 16. Third, in Islamic law, the imam of the school of law (conventional fiqih) allows marriage at an early age.  Pernikahan dini menjadi isu kontroversial di Kluet Timur, Aceh Selatan, sehingga menjadi perbincangan semua kalangan. Artikel ini mengkaji bagaimana Kantor Urusan Agama mengabulkan permohonan pernikahan usia dini dan bagaimana Undang-Undang Peniruan Hukum Islam mempengaruhi pernikahan anak usia dini. Bagaimana hukum Islam meninjau pernikahan dini? Membahas tesis ini melalui penelitian lapangan. Sumber data primer dan sekunder Menurut penelitian, Kantor Urusan Agama mempermudah pernikahan dini dengan memberikan surat dispensasi untuk persyaratan bekas Pengadilan Agama bagi umat Islam dan Pengadilan Negeri bagi non-Muslim. Kedua, untuk kepentingan keluarga dan rumah tangga, perkawinan hanya dapat dilakukan oleh calon mempelai yang telah mencapai umur yang ditentukan dalam Pasal 7 Undang-Undang Nomor 1 Tahun 1974, yaitu calon suami. minimal 19 tahun dan calon istri minimal 16 tahun. Ketiga, dalam hukum Islam, imam mazhab (fikih konvensional) membolehkan pernikahan di usia dini.